TINJUAN YURIDIS PENGATURAN ABORSI BERDASARKAN UNDANG-UANDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Edwin Capri Purba; Erdianto Effendi; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Abortion is a social phenomenon that has existed since then and until now this issue is still being debated that seriusyang where abortion is divided into two, namely, abortion caused by humans (abortion provokatus) and natural abortion (abortion spontanitus). While abrtus provokatus also into two, namely: abortions performed for medical reasons and abortions without a medical reason, which in its development can be categorized denagn abortion legal action with no indication of a crime.the government of the Republic of Indonesia to make a rule about abortion, which is where it is listed in the Code of Penal (Penal Code) listed in Section 283.299 346 s / d of Article 350 , in Law No. 39 of 1999 about Human Rights (HAM), which are listed in Article 50 and Article 53, but in Law No. 36 of 2009 on Health which is the replacement for the previous Health Act that where abortion is specifically regulated in article 75 s / d of Article 77. in the Indonesian Government Regulation No. 61 Year 2014 on Reproductive Health in which Borsi arrangements set out in Article 31, s / d of ArticleIn the expansion of legalized abortion can be divided into two, namely abortion on the grounds of medical emergency and the reasons rape victims abortion, but the applicability is only acceptable while on the grounds of rape victims experienced the pros and cons, even this can not be accepted by the physician in the IDI refused this is because it is contrary to the oath of a doctor, but it is also the clergy was also rejected on the grounds of man is God's creation and the right to determine the life and death of God's own just as well. In addition, the implementation of an abortion performed by a female rape victim can also rejection by sosialog and social circles by reason of Indonesian society still upholds the eastern culture, but although the application of these abortions were denied it can tetp dilakakukan because laws and regulations still allow it listed dala PP No. 61/2014 Article 35.Thus abortion already has rules contained in the positive law of the Republic of Indonesia and of explanations pengaturanya legal abortion only with alasal medical emergencies as well as by reason of a female rape victim. And the application of either abortion about medical emergency reasons or for reasons of rape who have their pros and cons can still be applied and it has no special settings.